Regional Overview of Orogenic Belts in Indonesia: Emphasis on the Occurrences of Thrust Wedge Systems - Aldo Febriansyah Putra; Salahuddin Husein (Berita Sedimentologi, 2019)
Regional overview to the thrust wedge systems in Indonesia attempts to compile and review geologic settings related to the development of basement uplift and fold-thrust belts. Overview will be represented in orogenic belts of different geologic settings: Langsa Fold-Thrust Belt (North Sumatra Basin), Banyumas Fold-Thrust Belt (Western Central Java), Kutei Basin, West Sulawesi Fold-Thrust Belt (Lariang-Karama Basins and Makassar Straits), Offshore Northern Banggai-Sula, Misool-Onin-Kumawa Ridge, Berau-Bintuni Basins, and Lengguru Fuld-Thrust Belt. Key ideas and discussions encompass surface structural geology, geomorphology, and subsurface geology. Aiming to draw the big pictures, the integrated approaches will elaborate the relationship of thrust wedge system with strike-slip faulting as adjoining structural province. Geomorphology will be the basis to construct regional structural maps, while seismic images and regional cross-sections will contribute to subsurface reconstructions. Synthesis will highlight similarities on geomorphic features, associated structures to thrust wedge system, Pliocene – Recent as critical time to orogenic building in Indonesia, geodynamic significance of strike-slip faulting, and geodynamic settings related to thrust wedge system in Indonesia. Thrust wedge orogenic belts share curvilinear thrust faults traces and intensive folding near mountain front. On the other hand, associated structures to thrust wedge include synclinal feature in thrust front, detachment folds, and transpressive transtensional fault reactivation. Strike-slip faults may act as separate or associated structures in thrust wedge orogeny. Separate strike-slip faults can be observed as Sumatran Fault, Palu-Koro Fault, Balantak Fault, and Tarera-Aiduna Fault that act in response to slip partitioning or shift in deformation. Reactivated faults and tear faults are considered as associated structures to thrust wedge system. Thrust wedge system develops in both subduction and collisional tectonics.